Prevalence of risk factors in cardiovascular patients in a Caribbean country: Age and sex differences - Sasha Ramkhelawan; Andrea Joseph; Ricardo Clarke (Elsevier, 2024)
Background/objectives: Cardiovascular disease (CVD) is the leading cause of death worldwide, however little is known about the prevalence of risk factors in the Caribbean country of Trinidad and Tobago. This study investigates the prevalence of major cardiovascular risk factors in patients with CVD in Trinidad and Tobago between two age groups - <60 years and ≥60 years - and determines if the prevalence differed with sex. Methods: Medical records of 151 patients with CVD admitted to a private hospital in Trinidad and Tobago between January 2015 and March 2021 were analyzed. Patients were divided by sex, and into two age groups: <60 years (young) and ≥60 years (elderly). Chi-squared and Mann-Whitney U tests were used to analyze five major cardiovascular risk factors: hypertension, diabetes, smoking, hypercholesterolaemia, and family history of coronary heart disease (CHD). Results: It was found that the prevalence of hypertension was higher in the elderly group, while smoking, hypercholesterolaemia and family history of CHD were more common in males than in females. The prevalence of different risk factors varied with sex in the age groups: diabetes and family history of CHD in the <60 age group, and smoking and hypercholesterolaemia in the ≥60 age group. These risk factors were more prevalent in males than in females within the age groups. Additionally, the mean age of females in the ≥60 age group was found to be greater than that of males in the same age group. Conclusions: Age and sex differences were observed in the prevalence of major CVD risk factors, which may influence the management of CVD in Trinidad and Tobago. Intervention strategies, such as health education and counselling programmes that are age- and sex-specific, are recommended.